(untitled) (Experimental biology, 2015)
Some bacterial strains 1АН, 20, 3, 19б, 213, 222, 13АН, 433, isolated from the rhizosphere of cotton plant showed high root colonizing ability, phytohormones producing and antiphytopathogenic activity. The possibility of using there rhizobacteria to control Verticillium dahliae is discussed.